QUALITY ASSESSMENT AND CORPORATE EFFICIENCY IN THE MANUFACTURING INDUSTRIES IN NIGERIA - Akopunwanne, Uzoma E.O. (Journal of Advanced Research in Entrepreneurship, Innovation and SME Management, 2020)
The aim of the study was to ascertain the nature of the relationship between Quality assessment and corporate efficiency in the manufacturing Industries in Nigeria. The population for the study was a total of 146 senior management and supervisors of the manufacturing industries in Nigeria. The sample size of 103 respondents was finally used for data analysis. We recommended that, the design and growth of quality assessment should be transparent and follow formats which clearly identify what is expected from the worker and how deviations from expectations are to be managed or corrected Performance measurement should emphasize on outcomes and goals of objectiveness of the organization. Such specifications should guide what is expected of the workers and the extent to which their performance matches with the requirement. And that consideration should also be given to other performance assessment indices such as relationship with others as it is evident that support and relational leveraging is critical to the performance of the workers and in the actualization of corporate efficiency